(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
JMGA Human Resources is an organization that provides various services to support the labour industry. They connect employers and employees and are commonly known as an employment agency. In addition to assisting job seekers in finding suitable job opportunities, hiring through a staffing agency has several advantages, such as reducing the number of applications employers need to sort through. The company values its clients and strives to foster positive relationships with both parties by continuously developing and implementing new ideas related to labour code laws and agency and company responsibilities. Their goal is to excel in the Manpower Services industry. Researchers used a qualitative method and conducted interviews to evaluate the feasibility of enhancing the HR management procedure. The results were shown for the current and improved procedures, specifically in hiring, resignation, filing of leave, and termination. The researchers suggested additional measures to make the process smoother and more efficient, including using email as a mode of communication, monitoring office equipment to avoid delays, expanding the office area to accommodate more people, and providing employees with a comfortable workspace. Based on observations, the company may experience some challenges, such as issues with office equipment and limited space to serve clients who visit in person. Therefore, the researchers recommend adding steps to the Hiring, Resignation, Filing of Leave, and Termination processes to enhance office procedures. They also suggest that the company implement measures to improve efficiency, such as using email, monitoring equipment, expanding the office area, and providing a designated area for each process to ensure its success.